Pengaruh Promosi Dan Kualitas Pelayanan Terhadap Pembelian Di Coffe Shop Kopi Teman Lama Kota Mojokerto - Prasetyo, Muhammad Iwan; Nersiwad; Verlandes, Yuliasnita (PT. Kreasi Karya Majakata, 2024)
This study aims to determine and analyze the effect of promotion and service quality on purchases at the coffee shop Kopi Teman Lama in Mojokerto City. The research method used is classified as associative quantitative. The sampling technique used is non-probability sampling, namely accidental sampling. Data collection in this study using a questionnaire found on 110 respondents. The data analysis method in this study uses instrument tests, classical assumption tests, and hypothesis testing. The results of this study indicate that promotion has a positive and significant effect on purchases at the coffee shop Kopi Teman Lama Mojokerto, service quality has a significant impact on purchases, promotion and service quality together have a significant influence on purchases with a percentage of influence of 57.6%.